How chronic anthropogenic noise can affect wildlife communities - Kok, Annebelle C. M.; Berkhout, Boris W.; Carlson, Nora V.; Evans, Neil P.; Khan, Nicola; Potvin, Dominique A.; Radford, Andrew N.; Sebire, Marion; Shafiei Sabet, Saeed; Shannon, Graeme; Wascher, Claudia A. F. (Frontiers in Ecology and Evolution, 2023)
Anthropogenic noise is a major pollutant in terrestrial and aquatic ecosystems. Since the industrial revolution, human activities have become increasingly noisy, leading to both acute and chronic disturbance of a wide variety of animals. Chronic noise exposure can affect animals over their lifespan, leading to changes in species interactions and likely altering communities. However, the community-level impacts of chronic noise are not well understood, which impairs our ability for effective mitigation. In this review, we address the effects of chronic noise exposure on communities and explore possible mechanisms underlying these effects. The limited studies on this topic suggest that noise can affect communities by changing the behavior and/or physiology of species in a community, which results in direct or knock-on consequences for other communities in the ecosystem. Major knowledge gaps remain due to the logistically complex and financially expensive nature of the long-term studies needed to address these questions. By identifying these gaps and suggesting approaches to address them, we provide a road map toward mitigating the effects of a noisy world.